A Review Of The Extractive Metallurgy Of Indium - C. E. T. White; J. A. Slattery (Society for Mining, Metallurgy & Exploration, 1983)
Although trace amounts of Indium are found in many ores, commercial production of the metal has come almost exclusively from residues, flue dusts and slags generated by Zinc recovery operations. Our paper attempts to summarize the various approaches used to recover Indium from these by-products. Some comments on production and price trends are Included as well as our views on future availability.